Roles and Functions of PPAT in The Practice of Land Registration - Muhromi, Saidul; Bhudiman, Budy; Fajri, Ibrahim (Universitas Ibn Khaldun Bogor, 2024)
The purpose of land registration in accordance with the implementation in article (3) of the Government Regulation Number 24 of 1997 Regarding Land Registration, is the purpose of the creation of an information puisat on land parcels so that the party who has been registered with the government can overwrite the data needed in carrying out the huikuim meingeinai plots of land and units of ruimah suisuin that have been registered. The implementation of land registration is in a way that both provides basic and administrative principles in the field of land management. The PPAT Deed is one of the data requirements for the maintenance of land registration data, so it must be made up so that it can be used as a basis for the registration of transfer and the provision of rights. Therefore, PPAT is responsible for intuitively examining the intuitive requirements for the legality of the relevant legal proceedings. Among other things, matching the data contained in a certificate with the lists available at the Land Office. This type of research is an empirical normative legal research, namely a scientific research method which in this case combines normative legal principles which are individually coupled with additional data or empirical research. . This normative-eimpirical research method also aims to implement the intuition of normative law (indang-uindang) in its action in every intuitive legal event that occurs in a society's situation. basic legal certainty, So article 19 of the UUPA laws regulates land registration.